A Sec-dependent effector, CLIBASIA_04425, contributes to virulence in ‘Candidatus Liberibater asiaticus’ - Zhang, Shushe; Wang, Xuefeng; He, Jun; Zhang, Song; Zhao, Tingchang; Fu, Shimin; Zhou, Changyong (Frontiers in Plant Science, 2023)
Citrus Huanglongbing (HLB) is the most destructive citrus disease worldwide, mainly caused by ‘Candidatus Liberibacter asiaticus’ (CLas). It encodes a large number of Sec-dependent effectors that contribute to HLB progression. In this study, an elicitor, CLIBASIA_04425 (CLas4425) triggering ROS burst and cell death in Nicotiana benthamiana was identified. Of particular interest, its cell death-inducing activity is tightly related to associated with its subcellular localization and the cytoplasmic receptor Botrytis-induced kinase 1 (BIK1). Compared to CLas infected psyllids, CLas4425 showed higher expression level in planta. The transient expression of CLas4425 in N. benthamiana and its overexpression in Citrus sinensis enhanced plant susceptibility to DC3000 Pseudomonas syringae pv. tomato DC3000 ΔhopQ1-1and CLas, respectively. Furthermore, the salicylic acid (SA) level along with the expression of genes NPR1/EDS1/NDR1/PRs in SA signal transduction was repressed in CLas4425 transgenic citrus plants. Taken together, CLas4425 is a virulence factor that promotes CLas proliferation, likely by interfering with SA-mediated plant immunity. The results obtained facilitate our understanding of CLas pathogenesis.